Language beyond language: comics as verbo-visual texts - Saraceni, Mario (2001)
The investigation proposed in this study is based on the consideration that the nature of "text" is currently undergoing a change whereby verbal components are increasingly being accompanied by visual components, and the two modes of expression co-exist side by side in the same texts. The Internet is symptomatic of this change, with its multi-modal texts, where words, pictures, and sometimes even sounds, interact with one another. One of the main issues that this thesis aims to address is that although the relationship between the verbal and the visual is not an entirely new area of study, what characterises traditional approaches is the fact that the two components have fundamentally been considered as separate entities, while the combination of words and pictures has generally been regarded as having the function of aiding comprehension. This thesis is based on the main hypothesis that the combination of verbal and visual components is a true interaction which creates a type of 'language' that is more than a simple sum of the two codes. This type of verbo-visual interaction characterises media as old as film and comics, both of which came into existence around a century ago. However, while film studies has become an established discipline, comics have never enjoyed much scholarly attention, their expressive potentials having gone largely overlooked, and the publications that deal with them having being essentially socio-historical accounts. This thesis aims to investigate the complex and sophisticated type of interaction between verbal and visual elements that takes place in comics, and suggests that a close scrutiny of this medium enables the researcher to understand better the way in which the verbal/visual interaction works. In doing so, it recognises the necessity for linguistics to expand the notion of 'language' beyond the traditional verbal boundaries and to incorporate other types of codes which exhibit 'language-like' properties. The theoretical discussion is guided by an eclectic approach as it draws from the fields of semiotics, text-linguistics and stylistics. Accordingly, rather than developing one single main analytical model, this study proposes smaller frameworks, one in each of the areas of study drawn from. Finally, the thesis also suggests ways of applying the theoretical finding for pedagogical purposes.